Talinum paniculatum (Jacq) Gaertn (Java ginseng) production using Vesicular-Arbuscular Mycorrhizal - Sulistiono Sulistiono (Hasanuddin University, 2017)
Soil pathogen is one of main problem in Java ginseng production in tropical field. This study was aimed to evaluate the impact of VAM application to Java ginseng tuber production. Application of VAM was conducted in various concentrations (0, 1, 2, and 3%) (w/w). Thin Layer Chromatography was used to detected saponin and spectrophotometry was used to determine total saponin. Biomass, the number of rotten tuber, and total saponin were determined after eleven months under greenhouse condition. Inoculation 3% of VAM can enhance the number of healthy and biomass Java ginseng tuber significantly. But the application of VAM did not increase total saponin content.